2013
DOI: 10.7314/apjcp.2013.14.1.453
|View full text |Cite
|
Sign up to set email alerts
|

Lack of any Association between Blood Groups and Lung Cancer, Independent of Histology

Abstract: Introduction: Lung cancer, the leading cause of cancer deaths, is divided into 2 main classes based on its biology, therapy and prognosis: non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). Many cases are at an advanced stage at diagnosis, which is a major obstacle to improving outcomes. It is important to define the high risk group patients for early diagnosis and chance of cure. Blood group antigens are chemical components on erythrocyte membranes but they are also expressed on a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
3
26
1
2
Order By: Relevance
“…These alterations are hypothesized to be important for the development of certain malignancies (26,27). However, data concerning the role of ABO blood groups in lung cancer are limited and inconsistent (28)(29)(30). In the present study, no significant difference was observed between patients with lung cancer and healthy controls in terms of the distribution of ABO blood types, which is similar to the study by Oguz et al (28), but different from that of Urun et al (29), who identified an association between non-O blood types and an increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations are hypothesized to be important for the development of certain malignancies (26,27). However, data concerning the role of ABO blood groups in lung cancer are limited and inconsistent (28)(29)(30). In the present study, no significant difference was observed between patients with lung cancer and healthy controls in terms of the distribution of ABO blood types, which is similar to the study by Oguz et al (28), but different from that of Urun et al (29), who identified an association between non-O blood types and an increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and pathological research found that lung cancer is heterogeneous (Oguz et al, 2013). To improve the diagnostic sensitivity and specificity, severed tumor markers, combined together could be more effective in the diagnosis of lung cancer.…”
Section: 4369 Clinical Observation On a Combination Of Serum Tumor Mmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the main type of lung cancer. NSCLC is often diagnosed at an advanced stage (Oguz,et al, 2013) so that patients have little prospect of effective and curative treatment, with 5-year survival rates of < 15% (Jemal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%